Program One Day One Mustahik (ODOM): Kolaborasi Mahasiswa dan LAZISMU dalam Penguatan Kepedulian Sosial Masyarakat Kota Makassar - Syahrul Nasarudin; Mega Mustika; Eza Ramadhani; Muhammad Asril Arafah S; Nursam, Nursam; Ainun Rezkiyah Sarif; Raihana, Raihana; Mawar, Mawar; Nurfadhillah, Nurfadhillah; Arman, Arman (CV. ITTC INDONESIA, 2025)
This community service activity was carried out as part of the implementation of the Al-Islam and Kemuhammadiyahan (AIK) course at Universitas Muhammadiyah Makassar. The purpose of the activity is to enhance students’ social awareness through collaboration with LAZISMU in the One Day One Mustahik (ODOM) program. This program is designed to directly distribute assistance to mustahik groups such as street children, orphanage residents, becak drivers, parking attendants, and underprivileged communities in Makassar City. The method used is Participatory Action Research (PAR), which emphasizes the active involvement of students in all stages of the activity, from planning and implementation to evaluation. A total of 50 boxed meals and 20 basic food packages were directly distributed to several target points with full support from the LAZISMU team. The results of the activity show an increase in social awareness, communication skills, and the strengthening of students’ empathy towards social realities. On the other hand, the beneficiary communities felt tangible benefits both materially and morally. This collaboration has proven effective as a model of community service that integrates Islamic values, character education, and social action. The ODOM program is recommended as a model for service-based learning to be sustainably implemented within the Muhammadiyah campus environment.